PUDARNYA KEINDAHAN WANITA YANG JAUH DARI KAEDAH ISLAM DALAM KARYA GRAFIS TEKNIK STENCIL PRINT - NOLA NOFRIALISKA ARNAS, Drs, Irwan, M.Sn., Drs. Ariusmedi, M.Sn. (Universitas Negeri Padang, 2017)
Orchid flowers have beautiful shapes, shapes and colors. The beauty of orchids triggers the author to make it the source of ideas in the work. Interest of the author to make orchids as an object in tapestry, because the flowers are exotic, attractive, beautiful and durable. Orchid flowers are scarce and even endangered, due to illegal forest encroachment. This final work using a combination of several techniques (Flat, Klim, Soumak, and Geordes) with embroidery techniques. Through the merger of some of the above techniques, can produce works in new look. Visual elements and principles of art are taken into account in realizing the work, so that the work looks interesting. After a long series of creation processes, there were seven tapestry works, including: Green Orchid, Orchid Fiber, Cattleya, Moon Orchid, Phalaenopsis Violecea, Dendrodium, Black Orchid.Keywords: Orchid Flower, Tapestri, and Embroidery